(untitled) (Kronika Bydgoska, 2012)
Edward Woyniłłowicz (October 13, 1847 to June 16, 1928) - son of Anna nee Wańkowicz and Adam, Syrokomla coat of arms. Owner of Puzów and Sawicze estate in Słuck county. He was the president of the Mińsk Agricultural Society and the Polish Circle in the State Council in tsarist Russia. Politician, economic and social activist, and generous patron. Together with his wife Olimpia nee Uzłowska - founder of the Church of Saints Simeon and Helen in Mińsk. After the treaty of Riga, in 1921, his estate found itself over the eastern border. In December 1921, he took up residence in Bydgoszcz in 23 (currently 4) Zamoyskiego Street. President of the Union of Poles of the Polish Eastem Frontier in Bydgoszcz, member of the supervisory board of the Joint-Stock Company Bydgoszcz Lloyd. In Bydgoszcz, he wrote his memoirs, and the First volume was published in Vilnius in 1931. The second one remains as a manuscript in the National Library. He was buried in the Old Fara Church Cemetery. His tombstone bears the inscription: ‘Chased away of this land by the Treaty of Riga, I had to tread on alien fields’. Since June 2006, it has been a symbolic tomb - the ashes of Woyniłłowicz were moved to the Capital city of Belarus, to the church funded by him. On the 84th anniversary of the death of Woyniłłowicz, the sąuare by the Polish Eastern Frontier Dormitory, between Chodkiewicza and Ogińskiego Streets, was named after him.